Heterogeneity of Bovine Peripheral Blood Monocytes - Hussen, Jamal; Schuberth, Hans-Joachim (Frontiers in Immunology, 2017)
Peripheral blood monocytes of several species can be divided into different subpopulations with distinct phenotypic and functional properties. Herein we aim at reviewing published work regarding the heterogeneity of the recently characterized bovine monocyte subsets. As the heterogeneity of human blood monocytes was widely studied and reviewed, this work focuses on comparing bovine monocyte subsets with their human counterparts regarding their phenotype, adhesion and migration properties, inflammatory and antimicrobial functions and their ability to interact with neutrophilic granulocytes. In addition, the differentiation of monocyte subsets into functionally polarized macrophages is discussed. Regarding phenotype and distribution in blood, bovine monocyte subsets share similarities with their human counterparts. However, many functional differences exist between monocyte subsets from the two species. In contrast to their proinflammatory functions in human, bovine non-classical monocytes show the lowest phagocytosis and ROS generation capacity, an absent ability to produce the proinflammatory cytokine IL-1 after inflammasome activation, and do not have a role in the early recruitment of neutrophils into inflamed tissues. Classical and intermediate monocytes of both species also differ in their response towards major monocyte-attracting chemokines (CCL2, CCL5) and neutrophil degranulation products in vitro. Such differences between homologous monocyte subsets also extend to the development of monocyte-derived macrophages under the influence of chemokines like CCL5 and neutrophil degranulation products. Whereas the latter induce the differentiation of M1 polarized macrophages in human, bovine monocyte-derived macrophages develop a mixed M1/M2 macrophage phenotype. Although only few bovine clinical trials analyzed the correlation between changes in monocyte composition and disease, they suggest that functional differences between human and bovine monocyte subsets are also reflected in their different clinical relevance for distinct diseases. In opposite to the human system, where higher blood cell number of non-classical monocytes were widely correlated with several human infectious and non-infectious diseases, higher counts of bovine intermediate monocytes are suggested as a potential biomarker for inflammatory responses post partum.